2009
DOI: 10.1200/jco.2009.22.3883
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Active Immunotherapy With Combination of Two Chimeric, Human Epidermal Growth Factor Receptor 2, B-Cell Epitopes Fused to a Promiscuous T-Cell Epitope in Patients With Metastatic and/or Recurrent Solid Tumors

Abstract: A B S T R A C T PurposeTo evaluate the maximum-tolerated dose (MTD), safety profile, and immunogenicity of two chimeric, B-cell epitopes derived from the human epidermal growth factor receptor (HER2) extracellular domain in a combination vaccine with a promiscuous T-cell epitope (ie, MVF) and nor-muramyl-dipeptide as adjuvant emulsified in SEPPIC ISA 720. Patients and MethodsEligible patients with metastatic and/or recurrent solid tumors received three inoculations on days 1, 22, and 43 at doses of total pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 32 publications
0
68
0
Order By: Relevance
“…The ADCC assay was performed as previously described (Kaumaya et al, 2009) using effector peripheral blood mononucleated cells, which were obtained from normal human donors and isolated by density-gradient centrifugation in Ficoll-Hypaque (Pharmacia Biotech, Piscataway, NJ). The cells were washed twice in RPMI 1640 with 5% fetal calf serum and then serially diluted in 96-well plates to give effector/target ratios of 100:1, 20:1, and 4:1.…”
Section: Igf-1r-mediated Invasion In Her2-positive Cancer Cellsmentioning
confidence: 99%
“…The ADCC assay was performed as previously described (Kaumaya et al, 2009) using effector peripheral blood mononucleated cells, which were obtained from normal human donors and isolated by density-gradient centrifugation in Ficoll-Hypaque (Pharmacia Biotech, Piscataway, NJ). The cells were washed twice in RPMI 1640 with 5% fetal calf serum and then serially diluted in 96-well plates to give effector/target ratios of 100:1, 20:1, and 4:1.…”
Section: Igf-1r-mediated Invasion In Her2-positive Cancer Cellsmentioning
confidence: 99%
“…using a bioluminescence cytotoxicity assay kit (aCella-TOX TM ), as previously described. 38 We found that cancer cell lysis was, indeed, significantly increased following treatment with our vaccine antibodies. The effects increased as the effector to target cell ratio increased, with the greatest effects being achieved at an effector to target cell ratio of 100:1, as shown in Figure 5.…”
Section: Downregulation Of Igf-1r Expression and Phosphorylation Aftementioning
confidence: 65%
“…62 We further validated combinatorial therapies targetingHER-2 and VEGF, 63 and demonstrated that immunotherapy with HER-2 and VEGF peptide mimics plus metronomic paclitaxel elicited superior anti-neoplastic effects in transplantable and transgenic mouse models of human breast cancer. 29 We recently translated our vaccine studies into a phase 1 clinical trial 38 and are presently conducting a new FDA-approved, NCIfunded phase 1/11b trial (NCT01376505) with an improved vaccine combination. These strategies possess the combined advantages of inhibiting multiple distinct receptors (HER-1:HER-2; HER-2:HER-2; and HER-2: HER3) to potentially overcome mechanisms of resistance to conventional HER-targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the preclinical work was performed in HER2/neu transgenic mouse models due, in part, to the fact that a murine homolog was not confirmed until the early 2000s [14][15][16], although other models were also employed (dog, guinea pig, rat, primate) [209][210][211][212][213][214]. The majority of these have focused on the extracellular domain of HER2/neu due, in large part to the high degree of homology of the intracellular kinase domain with other receptor tyrosine kinases both in and outside of the HER family [209,[215][216][217][218][219], although some strategies have included elements from the intracellular domain [213][214][215]. Indeed, cytotoxic T-lymphocytes directed against HER2/neu have been documented to react with HER3 and HER4 [220].…”
Section: Her2/neu Antigen-specific Immunotherapymentioning
confidence: 99%